Klasifikasi Penderita Penyakit Diabetes Berdasarkan Decision Tree Menggunakan Algoritma C4.5 - Rinci Kembang Hapsari; Bagas Aulifia Riski Putra Wahyu; Achmad Fayi Farozi; Caesario Putra Mahendra (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2023)
Diabetes is a metabolic disease characterized by high blood sugar levels (hyperglycemia) caused by a lack of insulin or the ineffectiveness of insulin in regulating glucose metabolism. In addition there are other factors that cause diabetes such as heredity, weight, age, blood pressure and so on. It is estimated that the death rate caused by diabetes will continue to increase every year. Treatment of diabetes can be done by controlling blood sugar levels, eating a healthy diet, exercising regularly, and if necessary, carrying out early checks to reduce the risk of developing diabetes. Therefore it is necessary to have an early diagnosis which is expected to reduce diabetes and reduce complications of diabetes in the future. One thing that can be done is to apply the method contained in data mining, namely utilizing the classification method using the C4.5 algorithm which can produce more accuracy. Classification can be used as early treatment of this disease. Algorithm C4.5 is an algorithm that is used to form a decision tree. From the test results, it produces a fairly large accuracy, namely 85% Precision of 92%, and Recall of 85%.